Free municipality experiments should (also) be understood using an innovation doctrine - Hjelmar, Ulf; Leth Jakobsen, Mads (Politica, 2021)
There is a long-standing Danish and Scandinavian tradition for free municipality experiments where municipalities are granted exemptions from legislation so that they can experiment with new welfare solutions. Despite a strong societal focus on the phenomenon, there is a need to qualify the governance doctrines decision makers can use to develop and evaluate free municipality experiments. Through an analysis of the idea behind free municipalities and the development and content of the Danish free municipality experiments, strengths and weakness are identified in the most relevant governance doctrines historically – bureaucracy, New Public Management and New Public Governance. However, this does not provide a full understanding of the innovative logic of the programs and the associated opportunities for governance. The article introduces an innovation doctrine as an additional management doctrine that can address the innovative logic and experimental behavior of political entrepreneurs at the local level and support policies and programs provided by the state.